Extruded corn, sorghum, and soybean meal for nursery pigs - B T Richert; Terry L Gugle; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1992)
Two experiments were conducted to determine the nutritional value of extruded corn, sorghum, and soybean meal (SBM) for nursery-age pigs. Experiment 1 involved 180 weanling pigs, with an average age of 22 d and average weight of 13.2 lb. Treatments were 1) corn-SBM-dried whey-based control, 2) extruded corn (Ecorn)-SBM, 3) Ecornextruded SBM (ESBM), 4) sorghum-SBM, 5) extruded sorghum (Esorghum)-SBM, 6) Esorghum-ESBM. Extrusion of the grains improved feed to gain (F/G) but reduced average daily feed intake (ADFI) in phase 1 (d 0 to 10). For phase 2 (d 10 to 24), phase 3 (d 24 to 38), and overall, corn supported greater average daily gain (ADG) and ADFI compared to sorghum. Extrusion of the grain reduced ADG and ADFI. Extrusion of SBM improved ADG and ADFI of pigs fed the extruded grains. Corn had greater DM and N digestibilities than sorghum, and extrusion increased DM and N digestibilities compared to ground grains. In Exp. 2, 192 pigs were used (average age of 22 d and 12.6 lb initial weight). Treatments were arranged as a 2 x 2 x 2 factorial, with main effects of grain source (corn vs sorghum), processing method (grinding vs extrusion), and soybean meal treatment (SBM vs ESBM). Contrary to Exp. 1, sorghum supported greater ADG and ADFI compared to corn for phase 1. Extrusion of the grains reduced ADFI in phase 1, phase 3. and overall and reduced ADG in phase 3 and overall. Extrusion of SBM improved ADG and ADFI with ground grains but reduced ADG and ADFI with extruded grains. Extrusion of the grains and SBM improved DM and N digestibilities. In conclusion, extruded corn and sorghum improved performance for d 0 to 10 postweaning, but reduced growth performance if fed for the entire nursery period.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Extrusion; Sorghum; Soybean meal; Corn; Nursery